2022
DOI: 10.1111/jdi.13824
|View full text |Cite
|
Sign up to set email alerts
|

Reimagining care for young adults living with type 1 diabetes

Abstract: Young adults living with type 1 diabetes often struggle to achieve what clinicians consider to be optimal levels of metabolic control. Despite the impact that this can have on a young person's future risk of complications, there are relatively few studies reporting new ways of organizing or delivering care to this cohort. In this article, we explore some of the reasons why young adult diabetes care is challenging, and describe approaches to "re-imagining" how care might be improved. The work is informed by the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Similarly, a recent survey found that one‐third of adults report foregoing, and 4 in 10 delaying, recommended medical treatment due to cost 7 . At the same time, patients with seemingly excellent ‘disease control’ and biomedical outcomes may reach these outcomes only at the expense of those aspects of life that make life worth living in the first place 8 . An older man on a diuretic for cardiac insufficiency may stop taking his grandchild fishing because of urinary incontinence.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Similarly, a recent survey found that one‐third of adults report foregoing, and 4 in 10 delaying, recommended medical treatment due to cost 7 . At the same time, patients with seemingly excellent ‘disease control’ and biomedical outcomes may reach these outcomes only at the expense of those aspects of life that make life worth living in the first place 8 . An older man on a diuretic for cardiac insufficiency may stop taking his grandchild fishing because of urinary incontinence.…”
Section: Introductionmentioning
confidence: 99%
“…They describe that to make care fit, patients and clinicians work together in designing care, making sure their plans maximally respond to the patient's unique situation and priorities and minimally disrupt the patient's lives and social networks. This is an ongoing and iterative process, where patients and clinicians continuously re‐evaluate whether care still fits in people's lives and whether people's lives can still be lived alongside these plans of care 8,12 …”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations